Changes in brain functional connectivity between on and off states and their relationship with cognitive impairment in Parkinson’s disease - Kaoru Kinugawa; Tomoo Mano; Kazuma Sugie (Scientific Reports)
Abstract Parkinson’s disease (PD) is characterized by motor and non-motor symptoms. Cognitive decline is crucial in disease progression and affect quality of life; however, their underlying mechanisms in PD remain unclear. We explored the relationship between cognitive impairment and functional connectivity (FC) using resting-state functional magnetic resonance imaging in 26 patients with sporadic PD, focusing on the changes in FC between on and off states. Cognitive function was assessed using the Mini-Mental State Examination (MMSE) score. The correlation between MMSE scores and changes in FC values during on and off states was assessed using Pearson’s correlation coefficient. The correlation between changes in FC during the on and off periods and cognitive function differed for each cognitive function item. MMSE memory scores were positively correlated with FC between the brainstem and the left cerebral hemisphere. MMSE attention scores were positively correlated with FC between the bilateral thalamus and frontal lobes and negatively correlated with FC between the left cerebral hemispheres. These findings may facilitate our understanding of the neural correlates underlying cognitive impairment in PD and help develop treatment strategies to preserve cognitive function.